2019
DOI: 10.1002/slct.201901764
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of H4Mn5O12 Nanotubes Lithium Ion Sieve and Its Adsorption Properties for Li+ from Aqueous Solution

Abstract: Li4Mn5O12 with nanotubes morphology was successfully prepared by hydrothermal and solid phase reaction. The as‐obtained adsorbent was determined by X‐ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscope (TEM) and N2 ad/desorption technologies. The characterization results indicated that spinel H4Mn5O12 took on two‐dimensional nanotubes morphology with the diameter of pore ∼200 nm, BET surface area is 92.997 m2⋅g−1, and the corresponding pore size centers at 3.4, 35.9 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Biosorption is highly effective in separation of organic and inorganic substances in soluble or insoluble forms from an aqueous solution through the utilization of low-cost biosorbent materials among other methods (Fomina and Gadd 2014). Most of the studies on lithium recovery from a mixture of diverse cations with high concentrations have been conducted by inorganic adsorbents such as H 4 Mn 5 O 12 nanotubes lithium ion sieve (Xu et al 2019), iron-doped lithium titanium oxides (Wang et al 2018), titanium type ion sieve (H x TiO 3 ) (Wang et al 2017), k-MnO 2 (Yoshizuka et al 2002;Kitajou et al 2006;Park et al 2012;Recepog ˘lu et al 2017Recepog ˘lu et al , 2018. To our best knowledge, no studies have been found in the literature regarding the synthesis of lithium sorption-capable biosorbents from lignocellulosic wastes.…”
Section: Introductionmentioning
confidence: 99%
“…Biosorption is highly effective in separation of organic and inorganic substances in soluble or insoluble forms from an aqueous solution through the utilization of low-cost biosorbent materials among other methods (Fomina and Gadd 2014). Most of the studies on lithium recovery from a mixture of diverse cations with high concentrations have been conducted by inorganic adsorbents such as H 4 Mn 5 O 12 nanotubes lithium ion sieve (Xu et al 2019), iron-doped lithium titanium oxides (Wang et al 2018), titanium type ion sieve (H x TiO 3 ) (Wang et al 2017), k-MnO 2 (Yoshizuka et al 2002;Kitajou et al 2006;Park et al 2012;Recepog ˘lu et al 2017Recepog ˘lu et al , 2018. To our best knowledge, no studies have been found in the literature regarding the synthesis of lithium sorption-capable biosorbents from lignocellulosic wastes.…”
Section: Introductionmentioning
confidence: 99%